PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KOMPETENSI DASAR PENGUKURAN LUAS RUANG MASING-MASING ELEMEN DEKORASI INTERIOR RUMAH TINGGAL, PERKANTORAN DAN RUANG PUBLIK - Muhamad Ichsan Tasrif (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This review of the literature looks at how students' learning outcomes can be improved by using problem-based learning (PBL) models to measure the area of different ornamental components in public, residential, and office environments. The review emphasizes how well PBL fosters in pupils a critical thinking, problem-solving, and practical skill set. It also covers the difficulties and possible fixes in putting PBL concepts into practice, including supplying sufficient resources, training teachers, and offering assistance to students. According to the review's findings, PBL can help students become more proficient at measuring ornamental aspects and have a better overall educational experience